Sagittal Subtalar and Talocrural Joint Assessment With Weight-Bearing Fluoroscopy During Barefoot Ambulation. (April 2015) - McHenry, Benjamin D.; Exten, Emily L.; Long, Jason; Law, Brian; Marks, Richard M.; Harris, Gerald
Background: Identifying talar position during ambulation has proved difficult as the talus lacks palpable landmarks for skin marker placement and more invasive methodologies such as bone pins are not practical for most clinical subjects. A fluoroscopic motion system was used to track the talus and calcaneus, allowing kinematic analysis of the talocrural and subtalar joints. Methods: Thirteen male subjects (mean age 22.9 ± 3.0 years) previously screened for normal gait were tested. A fluoroscopy unit was used to collect images at 120 fps during stance. Sagittal motion of the talocrural and subtalar joints were analyzed. Results: The intersubject mean and standard deviation values for all 58 trials of 13 subjects are reported. Maximum talocrural joint plantarflexion of 11.2 degrees (4.3 degrees of standard deviation) occurred at 11% stance and maximum dorsiflexion of −6.9 degrees (5.6 degrees of standard deviation) occurred at 85%. Maximum subtalar joint plantarflexion of 4.8 degrees (1.0 degrees of standard deviation) occurred at 96% stance and maximum dorsiflexion of −3.6 degrees (2.3 degrees of standard deviation) occurred at 30%. Talocrural and subtalar range of motion values during stance were 18.1 and 8.4 degrees, respectively. Conclusion: Existing fluoroscopic technology was capable of defining sagittal plane talocrural and subtalar motion during gait. These kinematic results compare favorably with more invasive techniques. This type of assessment could support more routine analysis of in vivo bony motion during gait. Clinical Relevance: Fluoroscopic technology offers improved sagittal plane motion evaluation during weight-bearing with potential application in patients with end-stage ankle arthritis, postoperative ankle replacements and fusions, and orthotics and braces.